Mass Manufactured Glass Substrates Incorporating Prefabricated Electron Transport Layers for Perovskite Solar Cells. Issue 6 (28th January 2019) - Smith, Benjamin; Troughton, Joel; Lewis, Anthony; McGettrick, James; Pockett, Adam; Carnie, Matthew; Charbonneau, Cecile; Pleydell‐Pearce, Cameron; Searle, Justin; Warren, Paul; Varma, Su; Watson, Trystan
Abstract: A commercially available glass substrate which incorporates both a fluorine‐doped tin oxide and compact TiO2 layer deposited through chemical vapor deposition that is commonly used in "solar control products, " is presented. The substrate, known commercially as Pilkington Eclipse Advantage, is designed for use as an infrared radiation control product and this is the first known instance of it being employed and extensively characterized for use as a mass manufactured n‐type contact in perovskite solar cells. Using this substrate with no additional compact TiO2 layer, perovskite solar cells with PCEs of up to 15.9% are achieved. These devices are superior in performance to those where the compact TiO2 is deposited via spray pyrolysis. The reproducibility and large scale manufacturing base already established with this substrate represents significant potential for solving the problem of upscaling a uniform and pinhole free n‐type compact TiO2 blocking layer. Abstract : Pilkington Eclipse Advantage is a commercially available glass substrate commonly used in solar (infrared radiation) control products. Acting as an electron transport layer the substrate achieved power conversion efficiencies of 15.9% when fabricated into perovskite solar cells. These devices are superior in performance to comparable cells where the compact TiO2 is deposited via conventional spray pyrolysis.